2021
DOI: 10.1021/acs.joc.1c01702
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of 4-Aryl-1,2,3-triazoles via I2-Promoted Cyclization under Metal- and Azide-Free Conditions

Abstract: We herein report an iodine-mediated formal [2 + 2 + 1] cyclization of methyl ketones, p-toluenesulfonyl hydrazines, and 1-aminopyridinium iodide for preparation of 4-aryl-NH-1,2,3-triazoles under metal-and azide-free conditions. Notably, this is achieved using p-toluenesulfonyl hydrazines and 1-aminopyridinium iodide as azide surrogates, providing a novel route toNH-1,2,3triazoles. Furthermore, this approach provides rapid and practical access to potent inhibitors of indoleamine 2,3-dioxygenase (IDO).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 48 publications
1
7
0
Order By: Relevance
“…10 Current methods for the preparation of 4-substituted-1H-1,2,3-triazoles include acid-mediated cycloaddition of nitroolefins and sodium azide, 11 Pd or Cu-catalyzed reaction of bromoolefins, anti-2,3-dibromopropanoic acids, or acetylenes with sodium azide, 12 reactions of in situ formed propargyl azides via the Banert reaction, 13 multicomponent reactions of aldehydes, nitroalkanes, and sodium azide, 14 or enolizable ketones, ammonium acetate, and 1-azido-4-nitrobenzene, 15 Ndeallylation of allyltriazoles, 16 reactions of β-azolylenamines with sulfonyl azides, 17a and N,N-dimethyl enaminones and tosyl azide, 17b as well as iodine-promoted cyclization of arylmethyl ketones, p-toluenesulfonyl hydrazide, and 1-aminopyridinium iodide. 18 4-Substituted-1H-1,2,3-triazoles are also putative reaction products of cycloaddition between hydrogen azide (hydrazoic acid, HN 3 ) and terminal alkynes. hydrazoic acid and phenylacetylene proceeds sluggishly at elevated temperatures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…10 Current methods for the preparation of 4-substituted-1H-1,2,3-triazoles include acid-mediated cycloaddition of nitroolefins and sodium azide, 11 Pd or Cu-catalyzed reaction of bromoolefins, anti-2,3-dibromopropanoic acids, or acetylenes with sodium azide, 12 reactions of in situ formed propargyl azides via the Banert reaction, 13 multicomponent reactions of aldehydes, nitroalkanes, and sodium azide, 14 or enolizable ketones, ammonium acetate, and 1-azido-4-nitrobenzene, 15 Ndeallylation of allyltriazoles, 16 reactions of β-azolylenamines with sulfonyl azides, 17a and N,N-dimethyl enaminones and tosyl azide, 17b as well as iodine-promoted cyclization of arylmethyl ketones, p-toluenesulfonyl hydrazide, and 1-aminopyridinium iodide. 18 4-Substituted-1H-1,2,3-triazoles are also putative reaction products of cycloaddition between hydrogen azide (hydrazoic acid, HN 3 ) and terminal alkynes. hydrazoic acid and phenylacetylene proceeds sluggishly at elevated temperatures.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Huang et al [92] . reported an iodine‐promoted three‐component synthesis of 4‐aryl‐1H‐1,2,3‐triazoles 89 via [2+2+1] cyclization reaction between methyl ketones, p‐toulenesulphonyl hydazides and 1‐ aminopyridinum iodide in DMSO (Scheme 46).…”
Section: Iodine Catalyzed/mediated Multi‐component Reactionsmentioning
confidence: 99%
“…Huang et al [92] reported an iodine-promoted three-component synthesis of 4-aryl-1H-1,2,3-triazoles 89 via [2 + 2 + 1] cyclization reaction between methyl ketones, p-toulenesulphonyl hydazides and 1-aminopyridinum iodide in DMSO (Scheme 46). This is noteworthy here that in this azide-free synthesis of 1,2,3-triazoles, azide was surrogated by the combination of p-toulenesulphonyl hydrazines and aminopyridinum iodide.…”
Section: Synthesismentioning
confidence: 99%
“…Huang et al [75] . explored a reaction methodology to form 4‐aryl‐ NH ‐1,2,3‐triazoles 31 in iodine promoted [2+2+1] type cyclization reaction among methyl ketone 28 , N ‐tosylhydrazine 29 , and 1‐aminopyridinium iodide 30 .…”
Section: Heterocyclic Synthesismentioning
confidence: 99%
“…Huang et al [75] explored a reaction methodology to form 4-aryl-NH-1,2,3-triazoles 31 in iodine promoted [2 + 2 + 1] type cyclization reaction among methyl ketone 28, N-tosylhydrazine 29, and 1-aminopyridinium iodide 30. This transformation proceeds in a single step and a metal-free, azide-free condition giving high to moderate yield.…”
Section: Triazolesmentioning
confidence: 99%